Kepemimpinan Transformasional dan Pemberdayaan Psikologis terhadap Komitmen Organisasi dan implikasinya Kinerja Pegawai - Deden Ramdhan (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2015)
The purpose of this study is to analyze and formulate the influence of transformational leadership, psychological empowerment, motivation and work culture of employees working either partially or simultaneously on job satisfaction and organizational commitment, and its implications for the performance of employees in Kandatel West Java. This research uses descriptive method and verifikatif with an emphasis on exploration and interpretation of the results of linkage analysis between variables through a hypothesis testing using path analysis. The data collection questionnaire used assistive devices. Sampling technique used is simple random sampling at each employee Kandatel, Kancatel and STO by the number of samples as many as 360 employees. The results of this study concluded that 1) transformational leadership, psychological empowerment, motivation and work culture of employees working either partially or simultaneously influence job satisfaction and organizational commitment, and 2) job satisfaction and organizational commitment of employees either partially or simultaneously affect the employee's performance Kandatel in West Java. Based on the conclusions found that psychological empowerment transformational leadership, work motivation, work culture, job satisfaction and organizational commitment directly and indirectly influence positively in improving the performance of employees in Kandatel West Java.